The effects of knowledge and innovation on regional growth: Nonparametric evidence - Marcos Sanso-Navarro; Maria Vera-Cabello (European Regional Science Association (ERSA), 2015)
This paper deals with the relationship between knowledge, innovation and regional growth. The study is carried out through the application of nonparametric estimation methods to European data at NUTS2 level. We provide evidence that the share of innovative ...firms plays a more relevant role in explaining regional growth than R&D expenditures. Further, inward FDI turns out to be a robust growth determinant. Our results also suggest that the effects induced by these variables are of a heterogeneous nature. As a byproduct of the analysis, we show that the estimation results from a local-linear kernel regression can be used for the identi...cation of spatial patterns. In this respect, we ...find a cluster of innovation-driven labour productivity growth in Germany.
Keywords: C14; C20; O18; R11; 330; Regional growth; knowledge; innovation; nonparametric methods; nonlinearities